Sex-related differences in hip and groin injuries in adult runners: a systematic review - Ross, B. J.; Lupica, G. M.; Dymock, Z. R.; Miskimin, C.; Mulcahey, M. K. (The Physician and Sportsmedicine, 2023)
Objectives Hip/groin running-related injuries (RRIs) are relatively uncommon. It is unclear if runners of either sex are disproportionately affected. Our objective was to systematically review differences in hip/groin RRIs between males and females.